A new research approach for Peace Innovation. Issue 2 (3rd July 2018) - Miklian, Jason; Hoelscher, Kristian
ABSTRACT: How can we foster more socially responsible pro-peace innovations that also have deeper impact? In arguing that incorporating contextual, area-specific and conflict-sensitive guidance enhances the quality and depth of innovation, this article calls for a new research approach on Peace Innovation (PI). This approach could help overcome four existing challenges: expanding the scholar–entrepreneur–policy triad of PI; prioritizing ethical, culturally sensitive engagement; designing innovation to more clearly deliver positive impacts in conflict environments; and glocalizing the PI playing field. We then explore five thematic areas where PI can be impactful: forecasting political economies of conflict; business and virtual peacebuilding; climate and environmentalism; migration and identity; and urbanization. Finally, we discuss how to operationalize such partnerships, moving the theoretical discussion on PI forward for both the peacebuilding and innovation communities. Pushing research frontiers forward will also help innovators develop better tools that prevent violence and promote peace in crisis and conflict environments.